How should we enhance the pre-departure and post-migration training program for Thai overseas migrant workers? - Naruchaikusol, S. (University of London, 2023)
This brief focuses on international labor migration through a bilateral agreement and pre-departure training program in four major destination countries. Migration has been a common strategy for rural households to cope with fluctuations in agricultural production and prices, land pressure, and income diversification. Internal labor migration between rural and urban areas is most often for work in construction, manufacturing and services in industrial estate areas in cities including Bangkok, Chiang Mai, Phitsanulok, Khon Kaen, Nakhon Ratchasima, Ayutthaya, Chonburi, and Rayong. Many people leave Thailand to find work abroad, where there are better income and job prospects.